NEGARA HUKUM INDONESIA BERDASARKAN ANALISIS YURIDIS NORMATIF TENTANG UNSUR-UNSURNYA - Zakir, Fauzan (Ensiklopedia of Journal, 2024)
The state view or state theory of a nation cannot be separated from a nation's outlook on life. This nation's view of life is what causes other nations' views of the state. Looking at the existing theories in state science, we will find 3 (three) types of human views on state life, namely: a) Individualistic state view, from this group several famous thinkers are known, such as Thomas Hobbes, John Locke and Jean Jaques Rousseau. b) The group state view according to class theory, this was put forward by Marx, Engels and Lenin. The term "class" is defined as a certain position or position in the production process, but it is called a social class if the group is recognized as a class, as a special group that is willing to fight for it. c) the integralistic view of the state was put forward by Adam Heinrich Muller, Spinoza and Hegell. In Indonesia's integralistic perspective (the concept of a family state), even though the interests of society take precedence over individual interests, the dignity of an individual is still respected. To be called a rule of law state, the following elements must be met: a) protection of human rights; b) separation or sharing of powers to guarantee these rights; c) every government action must be based on law; and d) the existence of administrative justice. Indonesia is a country of law, it can be simply answered that Indonesia is a country of law. The concept of a constitutional state in Indonesia has existed since the enactment of the 1945 Constitution. This is proven in the Explanation of the 1945 Constitution, which states that "The Indonesian state is based on law (Rechtsstaat) not based on mere power" (Machtsstaat). Keywords: Rule of Law, Indonesia